POLA KOMUNIKASI MASYARAKAT SUKU NUHATAN SEBAGAI DAMPAK AKULTURASI BUDAYA - Aulia Vera Rozida (Universitas Tribhuwana Tunggadewi, 2011)
This research aims to describe in detail and deeply the communication patterns in detached tribe society which experiencing of modernization as cultural acculturation impact, including: description of life Nuhatan Tribe; the communication pattern of Nuhatan Tribe before and after cultural acculturation, covering interpersonally,in group, organization, and mass communication; and also influence of acculturation to change at Tribe of Nuhatan. The research location is in Nuhatan Tribe, Sepa Village, Amahai District, Central Of Maluku Regency. This study is categorized into fundamental research type with qualitative descriptive method. The data was explored using in-depth interview, participatory observation and documentation. The writer gets the impression that (1) Life of Tribe of Nuhatan have experiencing of many change which because of existence of modernization and induce at the happening of cultural acculturation. But it is of course not all change affect positive at growth of society. (2) Before happened cultural acculturation, tribe society of Nuhatan use two communications pattern namely communications of interpersonally and in group communications. Communications pattern of interpersonally more dominant happened because society more is enjoying of communications entangling emotional contiguity. (3) The happening of cultural acculturation very having an effect on to change of Tribe society communications pattern of Nuhatan because the acculturation can influence patterned thinking and laid open behaviour with communications. (4) Cultural acculturation bring change to Tribe society communications pattern of Nuhatan, namely in this time they can use organizational communications pattern and mass, in order to make-up of social status and prosperity of society. But communications pattern which is just the run not yet application can better and give positive effect which significant.